Additional value of triple‐sensor urethral catheter in demonstrating urethral pressure variations during filling cystometry. Issue 8 (4th September 2019) - Kummeling, M. T.; Bovelander, E.; van Uhm, J. I.; van Koeveringe, G. A.; Elzevier, H. W.; Putter, H.; Groenendijk, P. M.
Abstract: Aims: During filling cystometry, urethral pressure variations (UPV) can be observed. The clinical relevance and a clear definition of this phenomenon are still a matter of debate. For further research and definition of UPV, it is important to determine how this condition can best be demonstrated. The purpose of this study is to compare continuous urethral pressure measurements with a single urethral‐sensor catheter and a triple urethral‐sensor catheter in demonstrating UPV. Methods: Seventy‐five adult female patients requiring urodynamic investigation enrolled in this prospective study. All patients underwent two series of filling and voiding cystometry. One series was performed with a dual‐air balloon sensor urodynamic catheter, the other series with a triple urethral‐sensor catheter. UPV were defined as urethral pressure drop exceeding 30 cmH2O. Results: The prevalence of UPV was 37.3% (28 out of 75 patients), more common than detrusor overactivity. The triple urethral‐sensor catheter was more sensitive than the single urethral‐sensor catheter: In eight patients UPV were demonstrated with both catheters and in 18 patients only in the measurement with the triple urethral‐sensor catheter. This difference in detection was significant ( P  < .001). Conclusion: There is an additional value in measurement with the triple urethral‐sensor catheter for demonstration of UPV during filling cystometry. Currently, continuous measurement of urethral pressure during filling cystometry and UPV is not defined within International Continence Society terminology. The single urethral‐sensor catheter is useful for a start, however, it demonstrates less than half of all UPV